Creating Disability-Inclusive ID System - World Bank (World Bank, Washington, DC, 2020)
Access to identification is a vital priority. In developing countries, persons with disabilities are among those most likely to face barriers in accessing government services such as health and rehabilitation, public transportation, education, voting, financial services, and economic opportunities. For women and girls with disabilities and other persons with disabilities with intersecting identities, these barriers are multidimensional. Addressing poverty among persons with disabilities and their families requires solutions that address their differentiated and sometimes complex needs, a precondition of which is possessing official proof of identity. This report provides a model of the continuous nature of the ID lifecycle, suggesting some illustrative approaches to designing a disability-inclusive ID process at any stage in the lifecycle. The ID lifecycle comprises five phases, each allowing for disability-inclusive interventions. The five phases are: (1) planning and design; (2) outreach and engagement; (3) enrollment; (4) use of ID; (5) and monitoring and evaluation. The cycle presents examples of continuous activities which should be regularly revisited to ensure that ID systems are accessible to people with disabilities regardless of the stage of implementation of the ID system. While not exhaustive, and recognizing that country contexts differ, this cyclical model can be a useful planning tool, much like that used across the world by electoral commissions for inclusive voter registration.